2017
DOI: 10.1371/journal.pone.0186520
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 inhibits angiogenesis in a rat model of endometriosis through the VEGFR-2-mediated PI3K/Akt/mTOR signaling pathway

Abstract: ObjectiveThis study aimed to investigate the link between the inhibitory effect of ginsenoside Rg3 on the ectopic endometrium growth and the VEGFR-2-mediated PI3K/Akt/mTOR signaling pathway, a mechanism known to inhibit angiogenesis and induce ectopic endometrial cell apoptosis.Materials and methodsA model of endometriosis was established by allotransplantation in rats. The rats were randomly divided into 5 groups: the ginsenoside Rg3 low-dose group (group A,5mg/kgBW/d of ginsenoside Rg3), the ginsenoside Rg3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…The PI3K/AKT/mTOR signaling pathway is involved in the antitumor effects of ginsenoside Rg3 in lung cancer cells ( Xie et al, 2017 ). Ginsenoside Rg3 inhibits angiogenesis in a rat model of endometriosis through the VEGFR-2-mediated PI3K/Akt/mTOR signaling pathway ( Cao et al, 2017 ). Recent studies also have revealed that activation of the PI3K/AKT pathway exhibits a protective effect in a mouse model of ALI.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway is involved in the antitumor effects of ginsenoside Rg3 in lung cancer cells ( Xie et al, 2017 ). Ginsenoside Rg3 inhibits angiogenesis in a rat model of endometriosis through the VEGFR-2-mediated PI3K/Akt/mTOR signaling pathway ( Cao et al, 2017 ). Recent studies also have revealed that activation of the PI3K/AKT pathway exhibits a protective effect in a mouse model of ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Neiyi Fang resisted EM through decreasing the expression of mRNA and protein of TGF‐β1 and can remarkably restrain the growth of ectopic endometrium and inhibit inflammatory response , which were all consistent with our findings. Currently, Gestrinone was the most frequently used drug for the treatment of EM, promoting apoptosis and inhibiting growth and angiogenesis of the ectopic endometrium . CNYP administration herein showed comparable benefits to Gestrinone in surgically induced EM rats in the context of USP10 expression and ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 67%
“…The anti-angiogenic effect of Rg3 is mainly due to the regulation of VEGF and suppression of the interaction between endothelial cells and the extracellular matrix by reducing the microvessel density in tumor tissues [ 111 , 112 ]. Ginsenoside Rg3 has been shown to inhibit angiogenesis in endometrial lesions in a rat model by blocking VEGFR-2 and inhibiting the PI3K/Akt/mTOR signaling pathway [ 113 ]. Rg3 has been shown to effectively alter the fibrotic properties of human embryonic stem cells (HESCs) in patients with endometriosis, likely via miR-27b-3p modulation [ 114 ].…”
Section: Resultsmentioning
confidence: 99%